Density functional calculations, electronic structure, and optical properties of molybdenum bimetallic nitrides Pt2Mo3N and Pd2Mo3N - Ali Hussain, Reshak, Prof. Dr.; Auluck, S.; Kityk, I. V. (American Chemical Society, 2011)
Link to publisher's homepage at http://www.acs.org/